2016
DOI: 10.2106/jbjs.15.00787
|View full text |Cite
|
Sign up to set email alerts
|

Arterial Anatomy of the Posterior Tibial Nerve in the Tarsal Tunnel

Abstract: Background: Both vascular and compression etiologies have been proposed as the source of neurologic symptoms in tarsal tunnel syndrome. Advancing the understanding of the arterial anatomy supplying the posterior tibial nerve (PTN) and its branches may provide insight into the cause of tarsal tunnel symptoms. The purpose of this study was to describe the arterial anatomy of the PTN and its branches. Methods: Sixty adult cadaveric lower extremities (thirt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 28 publications
0
12
0
Order By: Relevance
“…Anatomically, the posterior tibial nerve is a branch of the sciatic nerve that carries spinal roots L4-L6 and S1-S3 as the largest distal extension of the lumbosacral plexus. The pudendal nerve also originates from the sacral plexus along with the sciatic nerve 41 . Thus, our hypothesis can be supported by the role of the pudendal nerve, as it can interact with the stimulation signal from the tibial nerve.…”
Section: Discussionmentioning
confidence: 99%
“…Anatomically, the posterior tibial nerve is a branch of the sciatic nerve that carries spinal roots L4-L6 and S1-S3 as the largest distal extension of the lumbosacral plexus. The pudendal nerve also originates from the sacral plexus along with the sciatic nerve 41 . Thus, our hypothesis can be supported by the role of the pudendal nerve, as it can interact with the stimulation signal from the tibial nerve.…”
Section: Discussionmentioning
confidence: 99%
“…[ 5 7 8 ] It is noteworthy that PTN and its branches (MPN and LPN) are supplied by multiple blood vessels, often abnormally tortuous,[ 2 ] within the TT as they pass through different tight fibroosseous canals. [ 39 ] Fullerton and Gilliatt have shown that the plantar nerves are susceptible to repeated minor trauma. [ 40 ] In their elegant experimental study, they found that animals kept in confinement with the wire-mesh floor, developed demyelinating plantar neuropathy characterized by prolongation of the terminal latency and dispersion of CMAP, confirmed to be segmental demyelination in the nerve samples of those animals.…”
Section: Discussionmentioning
confidence: 99%
“…The malleolus canal is a brous bony channel behind the medial malleolus, with the anterior wall being the distal tibia, the posterior wall being the posterior talus and calcaneus, and the exor support band covering the surface. The anatomy of the tibial nerve and its major branches is largely determined by its position in the ankle canal [1]. The special anatomical structure and soft tissue space of the ankle canal makes the ankle canal syndrome the most common disease symptom in this area, and its occurrence is often closely related to the nerve compression [2,3].…”
Section: Introductionmentioning
confidence: 99%